Faidh al-Ihsānī Naskah Manaqib Syaikh Abduṣ Ṣamad al-Palimbānī - Kemas Andi Syarifuddin (Medina-te : Jurnal Studi Islam, 2021)
The main problems of this research are 1) What is the general description of Faidh al-Ihsani's manuscript through a philological approach? 2) How is the biography of Shaykh Abdus Samad al-Palimbani related to the existence of the Faidh al-Ihsani manuscript and how is the analysis of the contents of the text? This research uses philological research methods with stages. The data used are qualitative data obtained from primary and secondary sources. This type of research is a library research study by presenting a facsimile edition of the FI manuscript text, transliterating the original Arabic-Malay text into Latin and at the same time analyzing it. From the research findings, it is known that the FI manuscript is a single manuscript (codex unicus), which contains several mistakes and omissions in writing the manuscript, and there are writings that are forgotten to be written. The contribution of the Faidh al-Ihsani manuscript is very important for the preparation of writing the biography of Shaykh Abdus Samad al-Palimbani, including: First, before the Faidh al-Ihsani manuscript was discovered, the history of the biography of Shaykh Abdus Samad al-Palimbani that has developed so far is still confusing and there are several mistake. Second, thanks to the presence of the FI manuscript, by itself it can neutralize and straighten the history of Shaykh Abdus Samad al-Palimbani's life journey from local sources. Third, Shaykh Abdus Samad al-Jawi al-Palimbani is a great charismatic cleric from Palembang, a well-known Sufi and writer who has a wide range of scholarship in the international network of scholars. Fourth, in the Faidh al-Ihsani manuscript it is stated that Shaykh Abdus Samad bin Abdurrahman was born in Palembang in 1150 H or at the same time 1737 AD. Fifth, Regarding the work, works and teachings of Shaykh Abdus Samad al-Palimbani until now, we can still find them, His written works such as Hidayat as-Salikin, Sair as-Salikin, and others are still being read and studied. Likewise with his teachings, reading manaqib, tarekat remembrance, especially Ratib Samman, are still carried out and practiced by the Islamic community in general.